Environmental Factors That Influence Stem Cell Migration: An "Electric Field" - Stephanie N. Iwasa; Robart Babona-Pilipos; Cindi M. Morshead (Hindawi Limited, 2017)
Environmental Stimulus of Electric Fields on Stem Cell Migration. The movement of cells in response to electric potential gradients is called galvanotaxis. In vivo galvanotaxis, powered by endogenous electric fields (EFs), plays a critical role during development and wound healing. This review aims to provide a perspective on how stem cells transduce EFs into directed migration and an understanding of the current literature relating to the mechanisms by which cells sense and transduce EFs. We will comment on potential EF-based regenerative medicine therapeutics.